Čalbmi čalmmis ja suoldnečalmmit suoidnečalmmis: Sámegielaid singulatiivvat - Ylikoski, Jussi (Nordlyd, 2022)
North Saami čalbmi ‘eye’ (< Proto-Uralic *ćilmä) has cognates in all Uralic languages, and everywhere they refer to the visual organs of humans and animals. However, scholars have barely paid attention to the grammatical functions of čalbmi in compound-like formations such as suoldnečalbmi “dew eye”, suoidnečalbmi “grass eye”, varračalbmi “blood eye”, jiekŋačalbmi “ice eye”, vuoktačalbmi “hair eye” and muorječalbmi “berry eye”. This article examines such expressions as so-called singulatives – grammatical means for individuating a single referent from a group or mass (i.e., ‘a single drop of dew’, ‘a single blade of grass’, ‘a single drop of blood’, ‘a single crystal of ice’, ‘a single human hair’ and ‘a single berry’). The article mainly discusses morphological, syntactic and semantic features of singulatives in North Saami and other present-day Saami languages, but comparable singulatives in Khanty, Mansi and Samoyed languages as well as in Hungarian suggest that singulative expressions such as *weri-ćilmä ‘a single drop of blood’, *jäŋi-ćilmä ‘a single crystal of ice; hailstone’ and *me̮rja-ćilmä ‘a single berry’ can, in principle, be reconstructed all the way back to Proto-Uralic. Sámegiela čalbmi-substantiivvas leat etymologalaš vástagat buot urálalaš gielain, ja juohke sajis dat mearkkašit áicanorgána mainna olbmot ja eallit oidnet. Dattetge ovddit dutkit eai leat gidden olus fuomášumi dasa, makkár giellaoahpalaš funkšuvdna sámegiela čalbmi-elemeanttas lea dalle go dat geavahuvvo dajaldagain dego suoldnečalbmi, suoidnečalbmi, varračalbmi, jiekŋačalbmi, vuoktačalbmi ja muorječalbmi. Dát artihkal analysere dákkár dadjanvugiid nu gohčoduvvon singulatiivan, dihtolágan ávnnassániid ovttaidlogu hápmin. Artihkal guorahallá davvisámegiela lassin maiddái eanáš eará sámegielaid hui seammalágan singulatiivvaiguin. Sámegielaid singulatiivvaid morfologiija, syntávssa ja semantihka lassin guorahallo maiddái daid álgovuođđu, dasgo orru vejolaš jurddašit, ahte juo urálalaš vuođđogielas gávdnojedje – singulára, duála ...